1975
DOI: 10.4992/psycholres1954.17.119
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Amount of Required Coping Response Tasks on Gastrointestinal Lesions in Rats

Abstract: The effects of the coping response on gastrointestinal lesions by changing the values of fixed-ratio (FR) schedule for the coping response task in freeoperant avoidance situation over 24 hrs were studied. In FR 1 or FR 2, experimental animals which could control electric shock to avoid or escape by pushing a flapper only once or twice developed less severe gastrointestinal lesions and body weight loss than yoked animals which received the same amount of shocks but could not perform any coping responses. In FR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…It is likely that the consequences will be similar to those that have been found for traditional perceived control measures (e.g., locus of control, mastery, and self-efficacy). Perceived control is consistently shown to have health benefits for individuals across the life span (Schulz, Heckhausen, & Locher, 1991), and the early experimental studies convincingly demonstrated its linkage to autonomic reactivity and catecholamine levels, suppressed tumor rejection, and increased tumor growth and gastric ulceration (Bandura, Reese, & Adams, 1982; Sklar & Anisman, 1979; Tsuda & Hirai, 1975; Visintainer, Volpicelli, & Seligman, 1982).…”
Section: Health Consequences Of Sense Of Controlmentioning
confidence: 99%
“…It is likely that the consequences will be similar to those that have been found for traditional perceived control measures (e.g., locus of control, mastery, and self-efficacy). Perceived control is consistently shown to have health benefits for individuals across the life span (Schulz, Heckhausen, & Locher, 1991), and the early experimental studies convincingly demonstrated its linkage to autonomic reactivity and catecholamine levels, suppressed tumor rejection, and increased tumor growth and gastric ulceration (Bandura, Reese, & Adams, 1982; Sklar & Anisman, 1979; Tsuda & Hirai, 1975; Visintainer, Volpicelli, & Seligman, 1982).…”
Section: Health Consequences Of Sense Of Controlmentioning
confidence: 99%
“…Although the mechanisms involved in ulcerogenesis are not clearly understood, the development of gastrointestinal lesions is sensitive to behavioral and emotional factors (cf., Weiss, 1977). Immobilization (e.g., Brodie, 1963;Brodie & Hanson, 1960;Selye, 1936), conflict (e.g., Sawrey, Conger, & Turrell, 1956;Sawrey & Weisz, 1956;Weisz, 1957), and absence of control (e.g., Tsuda & Hirai, 1975;Weiss, 1968,197 la, 1971b have potent effects on ulcer development. Therefore, investigations examining the effects of predictable and unpredictable shock on gastric pathology must attend carefully to these variables.…”
Section: Gastrointestinal Pathologymentioning
confidence: 99%
“…In an experiment following up on Weiss's study of the effects of a coping response on stomach lesions, Tsuda and Hirai (1975) found that, compared with helpless yoked control rats, those that could escape the electric shock by a single bar press had fewer stomach lesions, but those that had to press the bar 10 times in order to escape had more lesions. From this, the formulation represented in Figure 14-10 would have to predict that the latter group would show more fear than their yoked controls by all of the other measures, including the CER and learning and performing a response to escape from the apparatus.…”
Section: Possible Shortcomings Of Simple Formulation In Terms Of Fearmentioning
confidence: 99%